Монета или белка? (К толкованию одного “темного места” в “Повести временных лет” - Синочкина, Б. (Kalbotyra, 1978)
The present paper gives a possible interpretation of the annals’ phrase побълъ и въверицъ meaning a size or the ancient tribute.Owing to the omision or intervals between words in old Russian manuscripts this expression can be understood in two ways: по бълъ и въвернцъ – conventional translation “a silver coin and a squirrel’s hide” or по бълъи въверицъ – “a squirrel’s white (winter) hide”.The author of the paper is of an opinion that the first segmentation of the phrase is more plausible from a linguistic viewpoint but considers the collocation a synonymous pair where both the word бъла and the one въверица denote by different terms the same object – squirrel’s hide.